Electron-configuration stabilized (W, Al)B2 solid solutions. (1st August 2019) - Hahn, Rainer; Moraes, Vincent; Limbeck, Andreas; Polcik, Peter; Mayrhofer, Paul H.; Euchner, Holger
Abstract: By combining experimental and theoretical methods, we have conducted a detailed study of the ternary diboride system (W1-x Alx )1-y B2(1-z) . Tungsten rich solid solutions of (W1-x Alx )1-y B2(1-z) were synthesized by physical vapor deposition and subsequently investigated for structure, mechanical properties and thermal stability. All crystalline films show hardness values above 35 GPa, while the highest thermal stability was found for low Al contents. In this context, the impact of point defects on the stabilization of the AlB2 structure type is investigated, by means of ab initio methods. Most notably, we are able to show that vacancies on the boron sublattice are detrimental for the formation of Al-rich (W1-x Alx )1-y B2(1-z), thus providing an explanation why only tungsten rich phases are crystalline. Graphical abstract: Image 1